Prevalence of Sydney Creases of Palmar Dermatoglyphic Patterns in Bangladeshi Down Syndrome Patient - Hossain, Mohammad Monir; Ashrafuzzaman, Md; Sultana, Sonia; Naher, Nurun (Bangladesh Journal of Anatomy, 2019)
Context: The Sydney crease is a proximal transverse crease that extends from beyond the hypothenar eminence to the ulnar margin of the palm. This study was to determine the prevalence of Sydney creases in Bangladeshi Down syndrome patient. Material and Methods: This cross-sectional observational analytical study was conducted in the department of Anatomy, Chittagong Medical College (CMC), Chattogram from January 2018 to January 2019. A total of 200 participants were included by convenient sampling according to inclusion and exclusion criteria. 100 Down syndrome patients were recruited in the study group. 100 medical and dental students of CMC were selected as control irrespective of sex. Dermatoglyphics print was taken by the ink and paper method. Result: Twenty three percent (23%) of patients had Sydney line in comparison to only 2% of the control (p<0.001) in both hand. The frequency of Sydney line in those with Down’s syndrome was significantly higher than in the corresponding controls p<0.001 in both hands. Conclusion: It is revealed that there are significant differences in frequencies of Sydney crease between Down syndrome patient and control group. Bangladesh Journal of Anatomy July 2019, Vol. 17, No. 2, 45-49